International Conference on Advanced Computer Theory and Engineering (ICACTE 2009) 2009
DOI: 10.1115/1.802977.paper49
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Modeling for Simulation: Steaming Frozen Food Processing in Vending Machine

Abstract: Nowadays, frozen foods are well-known among Malaysia society. This is due to the modern lifestyles which require short food preparing times without neglecting the food nutritious. In supporting this requirement, the manipulation of vending machine is identified as a tool to promote modern and healthy living style, besides to simplify the cooking process. This paper describes the effort on designing conceptual model for a proposed steaming food vending machine simulator. Conceptual modelling is the most crucial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Experiment results have shown that transforming Mealy FSM into Moore FSM increases the number of internal states, by a factor of 1.96 and increases the number of transitions by a factor of 2.05.This method is applied in engineering design. Zainuddin, et al [11], proposed a vending machine for steaming frozen food using conceptual modelling. The model reduced the amount of hardware required and the number of states needed.…”
Section: Related Workmentioning
confidence: 99%
“…Experiment results have shown that transforming Mealy FSM into Moore FSM increases the number of internal states, by a factor of 1.96 and increases the number of transitions by a factor of 2.05.This method is applied in engineering design. Zainuddin, et al [11], proposed a vending machine for steaming frozen food using conceptual modelling. The model reduced the amount of hardware required and the number of states needed.…”
Section: Related Workmentioning
confidence: 99%
“…Fauziah Zainuddin [5] proposes a VM, which has the basic procedures of FSM for serving food in appropriate way. Here, the researcher used three different features in his design they are user selection state, freezer state, and steaming state.…”
Section: Literature Reviewmentioning
confidence: 99%